Evaluation of Groundwater Quality in Spring Sources of Bauro Village, Lospalos Administrative Post, Lautém Municipality, Timor-Leste - Juvencio Dos Santos; Listyani Retno; Budiadi Budiadi (Journal Research of Social Science, Economics, and Management, 2025)
coli and total coliform, during field investigations at several spring locations. The results showed that whereas many spring sources satisfied acceptable drinking water criteria, several sites had higher than average levels of pollutants, underscoring the effects of human activities including inappropriate waste disposal and agricultural runoff. Overall water quality in these springs will be assessed using the Water Quality Index (WQI) standards consist of three core components, as there are three water quality parameters that help to measure the quality of water, which include physical parameters, chemical parameters, and biological parameters. The physical parameters include color, taste, odor, temperature, turbidity, solids, and electrical conductivity. which rated most samples as "good" for human consumption. However some sites to be treated before use water quality as well as pH, TDS, EC, Ion Content, BOD, in springs located in areas with high human activity will have worse quality parameters compared to springs located in more natural areas or areas with minimal human activity. Physical, chemical, and biological parameters of water in springs will show significant well to community in Bauro Vilage. The findings highlight the necessity of consistent monitoring and management techniques to preserve water quality and public health. This study advances our knowledge of the dynamics of water quality in spring sources and emphasizes how crucial sustainable water resource management is to preserving clean and dependable water supplies for communities who depend on these essential ecosystems.